1974
DOI: 10.1007/bf01965485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc ions on selective and nonselective histamine release in vitro

Abstract: The effect of different concentrations of zinc ions on the in vitro release of histamine from isolated rat peritoneal mast cells induced by compound 48/80 and Triton X-100, as well as the influence of the in vivo administration of zinc ions on the subsequent in vitro release of histamine from isolated peritoneal mast cells and lung tissue, have been investigated. The results show that intraperitoneal administration of zinc for 20 days significantly inhibited the spontaneous ~elease of histamine from lung tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…The ability of zinc sulphate to protect, dose-dependently, against reserpine-induced gastric ulcers can thus be explained by its primary inhibitory action on mast cell degranu lation (13)(14)(15) to prevent release of ulcerogenic agents (3 -5 , 17); this mechanism of action is therefore similar to that thought to be respon sible for its protective effects against stress ulcers (4 -7 ). Reduced histamine-mediated acid secretion would decrease ruminal ulceration; also, reduced mucosal vasodilatation and gastric contractions following depressed release of histamine and 5-hydroxytryptamine would lessen glandular ulcer formation.…”
Section: Discussionmentioning
confidence: 85%
“…The ability of zinc sulphate to protect, dose-dependently, against reserpine-induced gastric ulcers can thus be explained by its primary inhibitory action on mast cell degranu lation (13)(14)(15) to prevent release of ulcerogenic agents (3 -5 , 17); this mechanism of action is therefore similar to that thought to be respon sible for its protective effects against stress ulcers (4 -7 ). Reduced histamine-mediated acid secretion would decrease ruminal ulceration; also, reduced mucosal vasodilatation and gastric contractions following depressed release of histamine and 5-hydroxytryptamine would lessen glandular ulcer formation.…”
Section: Discussionmentioning
confidence: 85%
“…Zinc is an essential trace element for many biological processes in humans and animals. It has various regulatory functions such as inhibition of platelet aggregation and serotonin release [1], inhibition of histamine release from mast cells [2], inhibition of migration and phagocytosis by macrophages and polymorphonuclear leukocytes [3], and inhibition of granulocyte oxygen consumption and bactericidal activity against Escherichia coil [4]. Moreover, zinc may also function as a scavenger of endogenous free radicals [5].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc has been shown to influence many functions of various cells associated with the inflammatory process, including the inhibition of platelet aggregation and serotonin release [ 1] , inhibition of histamine release from mast cells [2], inhibition of macrophage and PMN migration and phagocytic activity [3], and inhibition of the production of prostaglandin and leukocyte mediators by stimulated rabbit PMN [25]. In cerulein-induced acute pancreatitis, the increase in pancreatic wet weight was significantly less in rats pretreated with anti-PMN than in the control rats [11].…”
Section: Discussionmentioning
confidence: 99%
“…* p <0.02; ** p <0.001 when compared with its corresponding salineinfused control, 'p <0.02 when compared with its saline-pretreated control. mast cells following vagal over-activity in stress, is based upon experimental evidence from rats indicating (a) that histamine is involved in stress ulcer formation (2,5) and is released from the gastric mast cells by stress (14) or by electrical vagal stimulation (3), and (b) that zinc prevents histamine release from the peritoneal mast cells (10,11). Recent observations have indeed shown that the ulcer-reducing effects of zinc are associated with its ability to prevent mast cell degranulation in the gastric glandular mu cosa of rats (15)(16)(17), and that these effects are accompanied by decreased histamine levels in the gastric secretion (18).…”
Section: Discussionmentioning
confidence: 99%
“…Since zinc sulphate pretreatment de creases gastric acid output and ulcer formation following electrical vagal stimulation (8 ,9 ), it is possible that these effects result from inhibition of histamine release from the mast cells (10,11) in the stomach. Using rat stomachs per fused in situ, the present study was undertaken to investigate the effects of zinc sulphate pre treatment on gastric acid secretion and lesion formation induced by intravenous infusions of methacholine.…”
mentioning
confidence: 99%